Meeting the challenges of biological threats and bioweapons in the 21st century - Ristanovic, Elizabeta; Burshaid Al-Dhaheri , Mubarak (Sociološki pregled, 2023)
Biological warfare has attracted people since the earliest times. During the Cold War, bio-weapons were part of the arsenal of both world superpowers. The Convention prohibiting the production, storage, transfer and use of potential biological weapons (BWC) was signed 50 years ago. The question arises how sincere the signatory states were in its implementation. The rapid development of molecular biology has raised awareness about its potential misuse in terms of creating new and more dangerous bio-weapons, as well as the question of ethics in biomedical research. The anthrax campaign in the USA represents a turning point after which the use of weapons of mass destruction (WMD), including biological ones, has become part of the narrative that accompanies each war conflict. Epidemics and pandemics of avian and swine flu, Zika virus, SARS, MERS and COVID-19, as well as their implications, have proved the significance of a multidisciplinary approach to the study of microorganisms, their epidemiological, microbiological, genetic and antigenic characteristics, methods of their diagnosis, prevention and treatment, not only from the biomedical, but also from the security aspect. Perhaps the 50th anniversary is the right time to ask why the International Expert Body for controlling the implementation of the BTWC provisions has not been constituted yet.